Consumers' body image expressions: Reflection of a Snow White or an Evil Queen - Wagner, Ralf; Singh, Swati (Frontiers in Psychology, 2023)
The aim of this paper is to explore how minimal-self impacts the body image, projecting it as a reflection of one’s approach towards their health and mental well-being. The study takes qualitative data from two countries India and Germany and draws on a qualitative study of 20 individuals who are involved in some kind of physical activity for a long time. This paper examines the body image perspectives from Grimms Brothers fairytale characters showcasing fit and healthy perspectives on Snow White side and projected and superfluous perspectives on Evil Queen side. The study also provides a model deciphering the rationale for both the reflections. Analysis shows that there is no clear white or black view of health and fitness projection via body image but it’s a gray line that gives wholesome fitness either a holistic mental peace or a competitive or success-oriented approach.